Roti Gambang sebagai Makanan Tradisional Betawi - Hana Dessy Natalina; Myrza Rahmanita; Saptarining Wulan (Ideas Publishing, 2023)
Roti gambang is a traditional Betawi food that has a high historical value. The study aims to identify the identity of the roti gambang as a traditional Betawi food and to show the attractiveness and interest of the public in consuming roti gambang as the Betawi traditional food. Descriptive qualitative research methods are used in this research with observational data collection techniques, library studies, interviews, and questionnaires. Research shows that Roti Gambang has existed since the Dutch colonial era but many people still do not know about it. However, the community has an interest and attraction in roti gambang so it has the potential to develop.